Quality Testing and Antioxidant Activity of Soap Contains Algae Extract Eucheuma spinosum - Juan Feren Salanti; Lidya Irma Momuat; Harry S.J. Koleangan (Sam Ratulangi University, 2022)
This study aimed to examine the quality and antioxidant activity of solid bath soap containing red algae extract E spinosum. Soap is made through a saponification reaction between a mixture of olive, palm and coconut oils (ratio 44:32:24%) with NaOH. In the saponification reaction, E. spinosum algae extract was added with 4 concentration formulations: 0, 0.050, 0.075, 0.1%. The soap produced is tested for it’s quality using the Indonesian National Standard (SNI) 3532:2021 which includes water content, pH, total fat, insoluble ingredients in ethanol, free fatty acids, chloride content, and unsaponifiable fat. The antioxidant activity of soap was tested using the DPPH method. The quality test results of each solid bath soap formulation, namely water content, pH, insoluble material in ethanol, and chloride content have met the quality requirements of SNI 3532:2021, while the total fat, free fatty acid, and unsaturated fat have not met the quality requirements of SNI. The antioxidant activity expressed in IC50 of each soap formulation is 463.3647 g/mL for formula A, 248.8397 g/mL for formula B, 155.5369 g/mL for formula C, and 90.3402 g/mL for formula D. This study concluded that solid bath soap containing E. spinosum extract did not meet the quality of SNI 3532:2021 and had antioxidant activity. Keywords: Antioxidant; Eucheuma spinosum; soap Pengujian Kualitas dan Aktivitas Antioksidan dari Sabun Mandi Padat Mengandung Ekstrak Alga Eucheuma spinosum ABSTRAK Penelitian ini bertujuan untuk menguji kualitas dan aktivitas antioksidan dari sabun mandi padat mengandung ekstrak alga merah E spinosum. Sabun dibuat melalui reaksi saponifikasi antara campuran minyak zaitun, sawit dan kelapa (rasio 44:32:24%) dengan NaOH. Pada reaksi penyabunan tersebut ditambahkan ekstrak alga E. Spinosum dengan 4 formulasi konsentrasi: 0, 0,050, 0,075, 0,100%. Sabun mandi yang dihasilkan diuji kualitasnya berdasarkan Standar Nasional Indonesia (SNI) 3532:2021 yang meliputi kadar air, pH, total lemak, bahan tak larut dalam etanol, asam lemak bebas, kadar klorida, dan lemak tak tersabunkan. Aktivitas antioksidan dari sabun diuji dengan metode DPPH. Hasil uji kualitas dari tiap formulasi sabun mandi padat yaitu kadar air, pH, bahan tak larut dalam etanol, dan kadar klorida telah memenuhi syarat mutu SNI 3532:2021, sedangkan untuk total lemak, asam lemak bebas, dan lemak tak tesabunkan belum memenuhi syarat mutu SNI. Aktivitas antioksidan yang dinyatakan dalam IC50 dari tiap formulasi sabun mandi yaitu 463,3647 µg/mL untuk formula A, 248,8397 µg/mL formula B, 155,5369 µg/mL formula C, dan 90,3402 µg/mL untuk formula D. Penelitian ini m enyimpulkan bahwa sabun mandi padat mengandung ekstrak E. Spinosum belum memenuhi kualitas SNI 3532:2021 dan memiliki aktivitas antioksidan. Kata kunci: Antioksidan; Eucheuma spinosum; sabun